MACROECONOMICS IN NEXUS OF OTHER COMPREHENSIVE INCOME AND ISLAMIC BANKS PROFITABILITY - Moh. Khoirul Anam; Marhaendra Kusuma; Abdul Hadi Bin Ahamad; Alfredo Dos Santos (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes. This study aims to analyze the moderating effect of macroeconomic fundamentals on the relationship between other comprehensive income to be reclassified (OCIR) and profitability.. Research Methods. Financial statement data from 71 Islamic banks across 10 Asian countries for the period 2016-2023, comprising 568 firm-year observations, were used. Moderated regression analysis was used to test the effect. Research Results and Findings. The test results indicate that OCIR has a positive effect on the profitability of Islamic banking entities, and macroeconomic fundamentals strengthen this effect. This result is consistent across different measurements of OCIR and profitability variables. An additional finding of this study is that OCIR has greater predictive power for future profits than the unreclassified OCI component. The implication of this study is input for investment analysis, especially those specializing in the Islamic finance industry, that OCIR, even unrealized earnings, also has value relevance due to its high predictive power of future profits, especially if the Islamic entity has many financial assets in the "available-for-sale" category. The originality of this research lies in examining the influence of OCIR on the profitability of Islamic banking entities in Asian countries and examining the moderating role of macroeconomic fundamentals.